Twitter Sentiment Analysis Based on Daily Covid-19 Table in Turkey - Kaya, Buket; Günay, Abdullah (My University, 2021)
The coronavirus epidemic, which began to affect the whole world in early 2020, has become the most talked about agenda item by individuals. Individuals announce their feelings and thoughts through various communication channels and receive news from what is happening around them. One of the most important channels of communication is Twitter. Individuals express their feelings and thoughts by interacting with the tweets posted. The aim of this study is to analyze the emotions of the comments made under the \"daily coronavirus table\" shared by the Republic of Turkey Ministry of Health and to measure their relationship with the daily number of cases and deaths. In the study, emotional classification of tweets was implemented using LSTM, GRU and BERT methods from deep learning algorithms, and the results of all three algorithms were compared with the daily number of cases and deaths.
Keywords: Deep Learnig